(untitled) (Bangladesh Journal of Physics, 2020)
Terahertz (THz) absorption spectra of poly 3-hydroxyalkanoates (PHB) for different conformations were investigated using molecular dynamics (MD) method. Temperature-dependent THz absorption spectra of PHB were measured over a temperature range of 10 K to 200 K. Peaks around (2.4-2.6THz) and (3.1-3.2THz) were observed due to vibrational transition of PHB, 1stpeaks are polarized perpendicular to c(┴)axis (along a, b axis) and next peaks are oriented parallel to the c(//) axis. The peak around (2.4-2.6THz) was assigned due to vibrational transition of PHB and C-H…O=C hydrogen bonds are oriented perpendicular to the c(┴) axis. We have also investigated orientation of the intermolecular hydrogen bonds by MD simulation and confirmed that it was mainly along the b axis of PHB. THz absorption spectra shifted to the lower frequencies and noticed widening of the absorption peaks that visualized from characteristics of peaks within creasing temperature, which is well reproduce of experimental observation. Bangladesh Journal of Physics, 26(2), 21-31, December 2019